Literature Review: Potensi Daun Sembung (Blumea balsamifera) sebagai Imunomodulator pada Hewan Percobaan - Ghoisya Zahiro Shofa (VitaMedica : Jurnal Rumpun Kesehatan Umum, 2025)
One chemical substance that can enhance the function and activity of the immune system is an immunomodulator. Immunomodulators can be found in various plants, including sembung leaves (Blumea balsamifera). This study aims to evaluate the potential of sembung leaf extract as an immunomodulator in experimental animals using a systematic literature review method. Articles were collected based on the keywords “immunomodulatory,” “sembung leaves,” and “body immunity” from the Google Scholar, Science Direct, and PubMed databases. The results of animal studies indicate that the administration of ethanol extracts of Sembung leaves at various doses has potential as an immunomodulator with anti-inflammatory, antipyretic, diuretic, and antidiarrheal effects. Additionally, Sembung leaf extracts have been shown to effectively inhibit bacterial growth and act as anti-inflammatory, diuretic, antipyretic agents, and anti-diarrheal.